DAMPAK TOXIC FRIENDSHIP DAN STRATEGI ANTISIPASI DALAM PERTEMANAN - Jesyinda Putri Wibowo; Zefanya Muri Putri Kristyanti; Talitha Fairuz Marsya Nugraha; Adelia Ananda Putri; Rijal Abdillah (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
The phenomenon of toxic friendship among university students is a significant issue because of its impact on mental health, academic achievement, and individual social abilities. This study aims to identify forms of toxic friendship, provide education about healthy friendship relationships, and develop prevention strategies based on religiosity values. The methods used included psychoeducation and observation, which were applied to students of Bhayangkara University, Greater Jakarta. The intervention results showed an increase in participants' understanding of the impact of toxic friendship and the ability to manage interpersonal relationships in a healthier manner. The programme also emphasised the importance of integrating religiosity values as a foundation in establishing positive friendship relationships. This study recommends ongoing programmes such as communication skills training, support group formation, and psychological consultation services to address these challenges.